Peningkatan Kemampuan Menulis Puisi Dengan Pendekatan Kontekstual Siswa Kelas IX SMP Negeri 1 Makassar - Syahyani, Ayu; Idawati, Idawati; Anwar, Anwar (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to improve the ability to write poetry with a contextual approach of class IX students of SMP Negeri 1 Makassar. This research is a Classroom Action research. The research subjects consisted of 40 students of class IX.2 SMP Negeri 1 Makassar. Data were collected through a poetry writing test, observation of student engagement, and interviews to find out students' responses to learning. Data were analysed quantitatively to measure the improvement of students' scores and qualitatively to understand changes in students' motivation and participation. The results showed that students in class IX.2 of SMP Negeri 1 Makassar could write poetry better with contextual learning method. This method successfully increased students' motivation and engagement. Their average score increased from 75 in cycle I to 85 in cycle II. By linking the learning materials with real world situations, students became more confident and creative in writing poetry.